(untitled) - Henderson, Fred (London, 1931)
An arresting study of our world economic confusion. Power production has carried us into a period of the constantly enlarged output derived from every hour of applied human effort...
Keywords: Machinery in the workplace,Máy móc tại nơi làm việc